2016
DOI: 10.1177/0969141315609634
|View full text |Cite
|
Sign up to set email alerts
|

Interval cancers using a quantitative faecal immunochemical test (FIT) for haemoglobin when colonoscopy capacity is limited

Abstract: The IC proportion was similar to that seen with guaiac-based FOBT. The later stage distribution of ICs highlights the benefits of lower f-Hb cut-offs, but with 19.4% of ICs having undetectable f-Hb, some cancers would have been missed, even with drastic reduction in the f-Hb cut-off.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
53
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 26 publications
8
53
2
1
Order By: Relevance
“…UK and other studies of population-based bowel cancer screening programmes [5][6][7][8][9][15][16][17] have consistently reported that interval cancers following negative faecal occult blood screening tests (both gFOBt and faecal immunochemical tests, FIT) tend to be found more often in women, in the right (proximal) colon and rectum, and to be of higher stage than cancers detected by screening; our results for site and stage are consistent with their findings (as is the overall sensitivity of screening). Our results also suggest that cancers of rarer morphologies (mucinous, signet ring cell, neuroendocrine and squamous) are more likely to be detected as interval cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UK and other studies of population-based bowel cancer screening programmes [5][6][7][8][9][15][16][17] have consistently reported that interval cancers following negative faecal occult blood screening tests (both gFOBt and faecal immunochemical tests, FIT) tend to be found more often in women, in the right (proximal) colon and rectum, and to be of higher stage than cancers detected by screening; our results for site and stage are consistent with their findings (as is the overall sensitivity of screening). Our results also suggest that cancers of rarer morphologies (mucinous, signet ring cell, neuroendocrine and squamous) are more likely to be detected as interval cancers.…”
Section: Discussionmentioning
confidence: 99%
“…3 The National Health Service (NHS) Bowel Cancer Screening Programme in England was started in 2006 and invites men and women aged 60-74 to complete a postal guaiac faecal occult blood test (gFOBt) every 2 years, with follow-up diagnostic testing (usually colonoscopy) for those who are FOB positive. 4 As in other similar programmes, UK screening sensitivity for cancer is about 50%: 5 that is, at each screen, about half of all colorectal cancers thought to be present in the screened population give rise to a positive FOB test and are detected. The remainder present symptomatically in the interval between one screen and the next.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study carried out by Digby et al[31] with FIT analyzing interval cancers, they concluded that the average value of f-Hb just before the round prior to the diagnosis of interval cancer (2.8 μgr f-Hb/g faeces) is much lower than the cut-off used most frequently in screening programmes (20 μgr f-Hb/g Faeces). In this study, by reducing the cut-off to 10 μgr f-Hb/g Faeces, the rate of positives would increase from 2.4% to 9.4%, with an important increase in the need for colonoscopies (increasing the number of false positives), which would increase the proportion of interval cancers by 38.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Of 24 669 responders, 450 had a positive screening test result and were referred for colonoscopy. In the two rounds of screening studied, the first with quantitative FIT using a threshold of ≥80 µg Hb/g faeces and the second using the standard guaiac faecal occult blood test/FIT two-tier reflex algorithm used in Scotland,3 the positivity in the first round was 2.5%: there were 30 screen-detected cancers (SDCs) and 31 interval cancers (ICs) 4. In the first round, 753 colonoscopies were performed.…”
mentioning
confidence: 99%